Effective Hospital Health Marketing Strategy: Literature Review - Salsabilla Anjani; Diansanto Prayoga (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: As a health service provider institution, hospitals are required to provide quality and reliable services following community expectations. Hospitals as one of the places to obtain services depend on the level of patient visits. Marketing mix and communication strategies become vital tools for hospitals and other healthcare institutions to build relationships with patients increase enrollment, ensure efficient and effective healthcare services. Objective: The literature review aims to provide alternative solutions for consumers or hospital patients to decide and choose a service in the hospital and find out the digital marketing optimization strategy that applies in the hospital. Result: The marketing mix and digital marketing overlap with each other. In the case of digital marketing, it can be seen that, the function of digital marketing in each hospital is as input and suggestions related to services at the hospital, it proves that, the role of digital marketing is very large to build reputation and services at the hospital. There is a positive correlation or relationship between digital marketing and the level of service satisfaction in the community or patients in the hospital. Conclusion: Healthcare marketing strategies can implement digital marketing because it can make it easier for patients to communicate with the public. Social media can also be an important tool to expand communication with patients and the public. Marketing strategies can also be carried out using digital marketing. To be accessible to all people and to make it easier for them to get information.